Globalization, violence and security: local impacts of regional integration - Espinosa, Shirlita; Fazio, Antonella; Fazio Vargas, Antonella (Regional integration and social cohesion, 2016)
Preface / Harlan Koff -- Violence and the production of knowledge -- Violence : global solutions to a global problem? / Vanessa Barolsky -- Aportes de la televisión a la formación ciudadana en el contexto de las violencias del sistema de salud en Colombia / Claudia Puerta Silva & Alejandro Agudelo Calle -- Violence and the city -- Resituar la ciudad : conflicto violento, conflicto armado y paz / Carlos Mario Perea -- From the desire to live to the readiness to kill : the result of legal and extra-legal punitive practices involving children and adolescents in Rio de Janeiro / Joana Domingues Vargas & Natasha Elbas Neri -- Violence, identities and development -- Regional mining identities vs. multinational mining -- Interests : the end of traditional small-scale gold mining in Marmato (Caldas, Colombia) / Robert V.H. Dover, Paula A. Hinestroza Blandón & Gloria Patricia Lopera Mesa -- Analyse comparée du phénomène de la violence contre les migrants au Maroc et au Mexique, pris dans le contexte des processus d'intégration régionale / Émeline Nanga -- About the authors